ПОНЯТТЯ «ІНТЕРПРЕТАТОРСЬКА КОМПЕТЕНТНІСТЬ» У СУЧАСНОМУ МУЗИЧНО-ПЕДАГОГІЧНОМУ ДИСКУРСІ - Лі, Чжау (Збірник наукових праць Уманського державного педагогічного університету, 2020)
У статті на основі аналізу широкого кола музично-педагогічних досліджень дано визначення поняття «інтерпретаторська компетентність» як комплекса фахових, соціальних, психологічних та естетичних якостей творчої особистості, спрямований на осягнення багатозначного художньо-образного змісту та інтонаційного сенсу музики в процесі індивідуальної виконавської діяльності; система ціннісних орієнтацій, звичок, уподобань, сформованих в процесі професійної підготовки співака під впливом певних національних, соціокультурних, економічних, політичних, ментальних чинників, які спрямовані на відтворення художньо-естетичного змісту музики шляхом творчо-виконавської реалізації особистості. В статье на основе анализа широкого круга музыкльно-педагогической литературы дано определение понятия «интепретаторская компетентность» как комплекса профессиональных, социальных, психологических и эстетических качеств творческой личности, направленного на постижение многозначного художественно-образного содержания и интонационного смысла музыки в процессе индивидуальной исполнительской деятельности; система ценностных ориентаций, привычек, вкусов, сформированных в процессе профессиональной подготовки певца под влиянием определенных национальных, социокультурных, экономических, политических, ментальных факторов, которые направлены на воссоздание художественно-эстетического содержания музыки путем творческо-исполнительской реализации личности. In article on the basis of the analysis of a wide range of musical and pedagogical literature are defined a determination of «competency in interpretation» as a complex of professional, social, psychological and aesthetic qualities of the creative person, aimed at the realization of multivalued artistic content and intonation of the meaning of music in the process of individual performance; the system of value orientations, habits, tastes, formed in the process of professional training of the singer under the influence of certain national, social, cultural, economic, political, mental factors, which aims to recreate the artistic and aesthetic content of music by creative and performing implementation of personality. Based on a set of authoritative scientific studies to determine the nature of the terms «competence» and «interpretation» and their definitions, we propose to consider the meaning of «competency in interpretation» as a set of professional, social, psychological and aesthetic qualities of the creative person, aiming to grasp the ambiguous artistic and imaginative intonation content and meaning of music in the performance of the individual; system of values, habits, preferences, formed in the process of preparation of the singer influenced certain national, cultural, economic, political, mental factors, which are aimed at artistic and aesthetic play music content by implementing creative and performing personality.